PENGARUH KEBIJAKAN, KESADARAN, PELAYANAN DAN INFORMASI TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK PADA KPP PRATAMA SURAKARTA - Nanda Aricha Pratami, Sri Hartono & Eny Kustiyah (Universitas Slamet Riyadi, 2017)
This research is motivated by the new policy the tax amnesty program, one of thepolicy objectives namely to encourage taxpayer who previously did not obey be obedientin the future. Then the purpose of this study was to determine the effect of policy taxamnesty, awareness, information and services tax amnesty on tax compliance together,knowing the effect of policy tax amnesty on tax compliance, determine the effect ofawareness of taxpayers on tax compliance, determine the effect services on taxcompliance and tax amnesty determine the effect of information on tax compliance. Thestudy population was 3,475 taxpayers to follow tax amnesty program on STO Surakarta.A sample of 100 taxpayers with accidental sampling technique. Analysis of the data usedin this study using multiple regression analysis, validity, reliability test, classicassumption test, the coefficient of determination (R2 test), regression test stimultan (Ftest), and partial regression test (t test). The results showed that the tax amnesty policy,awareness, information and services tax amnesty jointly influence on tax compliance onSTO Surakarta. Based on the results of data analysis known that the tax amnesty policyand no significant negative effect on tax compliance.Awareness of the taxpayer does nothave a significant effect on tax compliance. Services and significant positive effect on taxcompliance. Information tax amnesty positive and significant impact on tax compliance.Keywords: tax amnesty policy, awareness, services, information tax amnesty, taxcompliance.